Antibacterial phage ORFans of Pseudomonas aeruginosa phage LUZ24 reveal a novel MvaT inhibiting protein - Wagemans, Jeroen; Delattre, Anne-Sophie; Uytterhoeven, Birgit; De Smet, Jeroen; Cenens, William; Aertsen, Abram; Ceyssens, Pieter-Jan; Lavigne, Rob (Frontiers in Microbiology, 2015)
The functional elucidation of small unknown phage proteins (‘ORFans’) presents itself as one of the major challenges of bacteriophage molecular biology. In this work, we mined the Pseudomonas aeruginosa infecting phage LUZ24 proteome for antibacterial and antibiofilm proteins against its host. Subsequently, their putative host target was identified. In one example, we observed an interaction between LUZ24 gp4 and the host transcriptional regulator MvaT. The polymerization of MvaT across AT-rich DNA strands permits gene silencing of foreign DNA, thereby limiting any potentially adverse effects of such DNA. Gel shift assays proved the inhibitory effect of LUZ24 gp4 on MvaT DNA binding activity. Therefore, we termed this gene product as Mip, the MvaT inhibiting protein. We hypothesize Mip prevents the AT-rich LUZ24 DNA from being physically blocked by MvaT oligomers right after its injection in the host cell, thereby allowing phage transcription and thus completion of the phage infection cycle.